The electronic structure and the formation of polarons in Mo-doped BiVO4 measured by angle-resolved photoemission spectroscopy. Issue 27 (17th May 2019) - Mohamed, Mansour; May, Matthias M.; Kanis, Michael; Brützam, Mario; Uecker, Reinhard; van de Krol, Roel; Janowitz, Christoph; Mulazzi, Mattia
Abstract : Experimental investigation of the electronic structure of Mo-doped BiVO4 high-quality single-crystals with synchrotron radiation-excited angle-resolved photoelectron spectroscopy (ARPES). Abstract : We experimentally investigated the electronic structure of Mo-doped BiVO4 high-quality single-crystals with synchrotron radiation-excited angle-resolved photoelectron spectroscopy (ARPES). By photon-energy dependent ARPES, we measured the bulk-derived valence band dispersion along the direction normal to the (010) cleavage plane, while the dispersion along the in-plane directions is obtained by angle-dependent measurements at fixed photon energy. Our data show that the valence band has a width of about 4.75 eV and is composed of many peaks, the two most intense have energies in good agreement with the theoretically calculated ones. A non-dispersive feature is observed in the fundamental gap, which we attribute to quasiparticle excitations coupling electrons and phonons, i.e. polarons. The determination of the polaron peak binding energy and bulk band gap allows to fix the value of the theoretical mixing parameter necessary in hybrid Hartree–Fock calculations to reproduce the experimental data. The attribution of the in-gap peak to polarons is strengthened by our discussion in the context of experimental transport data and ab initio theory.